2022
DOI: 10.3390/bios12080589
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Framework for Detecting COVID-19 Infection Using Surface-Enhanced Raman Scattering

Abstract: In this study, we explored machine learning approaches for predictive diagnosis using surface-enhanced Raman scattering (SERS), applied to the detection of COVID-19 infection in biological samples. To do this, we utilized SERS data collected from 20 patients at the University of Maryland Baltimore School of Medicine. As a preprocessing step, the positive-negative labels are obtained using Polymerase Chain Reaction (PCR) testing. First, we compared the performance of linear and nonlinear dimensionality techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In this study, targeted plasma metabolomics combined with ML was proven to provide the rapid discrimination of SARS-CoV-2-positive and negative patients [ 18 ]. Further studies also focused on the identification of serological signatures of SARS-CoV-2 infection [ 19 ], the use of MALDI-TOF-MS, surface-enhanced Raman scattering (SERS), LC-MS, and MALDI-MS for the detection of SARS-CoV-2 in human saliva, nasal swabs, plasma and serum samples [ 20 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, targeted plasma metabolomics combined with ML was proven to provide the rapid discrimination of SARS-CoV-2-positive and negative patients [ 18 ]. Further studies also focused on the identification of serological signatures of SARS-CoV-2 infection [ 19 ], the use of MALDI-TOF-MS, surface-enhanced Raman scattering (SERS), LC-MS, and MALDI-MS for the detection of SARS-CoV-2 in human saliva, nasal swabs, plasma and serum samples [ 20 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…For transforming the high dimensional spectral data into a data set with reduced dimension, we used an unsupervised statistical technique, the principal component analysis (PCA) [44,45]. We have previously used PCA approach for Raman spectral analysis [46,47]. PCA result (Figure 3f) showed that the first principal component (PC1) can distinguish between single nanoparticles (+PC1 values) and multiple particles (-PC1 values) in a hyperspectral image.…”
Section: Resultsmentioning
confidence: 99%
“…44,45 We have previously used PCA approach for Raman spectral analysis. 46,47 PCA result (Fig. 3f) showed that the rst principal component (PC1) can distinguish between single nanoparticles (+PC1 values) and multiple particles (ÀPC1 values) in a hyperspectral image.…”
Section: Resultsmentioning
confidence: 99%
“…The SVM outperformed other techniques in the identification of cyanobacteria, using SERS spectra of mutant and wild-type strains [ 388 ]. Using a dimensionality reduction technique, followed by a probabilistic ML model, SARS-CoV-2 identification was performed with an accuracy of ~85% [ 389 ]. SERS coupled with SVM was also used for the identification of lung cancers [ 96 ].…”
Section: Machine Learning In Sers-based Biosensingmentioning
confidence: 99%